CHARACTERISTICS OF WATER QUALITY IN LAKE SHIKINAWA OF FUKUOKA, JAPAN - N. V. Tuan; K. Mori; Y. Hirai (Lowland Technology International, 2008)
Water quality is one of the main characteristics of water storage reservoirs or lakes. A water quality profile, in both of spatial and temporal variations, plays a very important role in assessment and management of lake water quality. In order to understand the lake water quality parameters, some observation plans were carried out for Lake Shikinawa, in different climate conditions including summer, typhoon occurring time, end of autumn, and before spring. Results of the first observation, which were done in summer, are presented and discussed in this paper. Some important properties of water quality situation of Lake Shikinawa were obtained and analyzed. Measured data also gave a clear understanding of the relationship among water quality parameters, effects of climate condition and aquatic plant coverage on lake water quality distribution. Besides, periods predominated by activities of convection term and wind induction on water quality were cleared from analyzed data.